Local political corruption and M&As - LIU, Chun (Institutional Knowledge at Singapore Management University, 2021)
We examine the relation between local political corruption and firms' cross-province M&As using provincial-level data on corruption in China. The results show that firms in more corrupt regions are less likely to engage in cross-province M&As. Further analyses reveal that the effects of local corruption on the probability of cross-province M&As are stronger when corrupt officers have greater impeding benefits or lower impeding costs. Meanwhile, Both ex-ante intervention and ex post punishment are important channels through which corrupt officers hinder firms' cross province M&As. Moreover, informal institutions, such as social capital and informal networks can help to alleviate the negative impact of political corruption on firms' cross-province M&As. Our findings show that in the context of highly government intervention, cross-province M&As not only cannot be an effective channel to shield from expropriation, but are themselves highly distorted and lead to significant economic efficiency losses.